Environmental determinants of life expectancy at birth in Turkey - Taşkaya, Serap; Demirkiran, Mustafa (International Journal of Research in Medical Sciences, 2016)
Background: Information on determinants of life expectancy has gained great importance due to the fact that life expectancy has been considered as the major health system outcome. Although social, economic and health-related factors of longevity have been investigated by some researchers, studies were undertaken on environmental determinants of lifespan are still inadequate. The aim of this study was to evaluate the environmental determinants of life expectancy at birth in Turkey. Methods: The research population constitutes 81 provinces in Turkey. Data were gathered from the Turkey statistical institute for the year of 2015. Air pollution, forest area, safe water and noise pollution were indicators of environmental health. OLS regression analysis was performed to investigate the relationship between dependent and independent variables by using Eviews 9 program. Results: At the end of analyses, it was found out that, the life expectancy at birth was affected by forest area per km2. Also, the results indicated that air pollution, access to safe water and noise pollution were not associated with life expectancy at birth. Conclusions: Forest area is one of the main issues for the healthy life of the country. These results are expected to provide evidence-based information to health policymakers to understand the environmental determinants of life expectancy at birth in Turkey.